Shaping a humane world : civilizations, axial times, modernities, humanisms - Kozlarek, Oliver; Rüsen, Jörn; Wolff, Ernst (Being human (Bielefeld, Germany) ;, 2012)
The generation of meaning is the primary precondition for acting and thinking. The essays in this volume contribute to a discourse on this matter with a decentred, globalized world in mind. The notions civilization, humanism and modernity - far from being exclusively Western ideas - may facilitate joint efforts of reflecting on the universality of current human conditions, particularly since such reflexion is possible from particular cultural perspectives. Modernity presents us with a second Axial Time in which the quest for a plural, but shared, humane world is the challenge.